2020
DOI: 10.1001/jamaoncol.2019.3692
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Tolerability of Pertuzumab, Trastuzumab, and Docetaxel for Patients With Early or Locally Advanced ERBB2-Positive Breast Cancer in Asia

Abstract: Prospective assessment of treatments known to benefit patients in global clinical trials in specific racial groups is essential.OBJECTIVE To compare the efficacy, safety, and tolerability of adding pertuzumab to trastuzumab and docetaxel vs placebo, trastuzumab, and docetaxel in Asian patients with ERBB2-positive early or locally advanced breast cancer. DESIGN, SETTING, AND PARTICIPANTSThis multicenter, double-blind, placebo-controlled phase 3 trial enrolled 329 women with ERBB2-positive early (T2-3, N0-1, M0)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
152
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(170 citation statements)
references
References 11 publications
15
152
3
Order By: Relevance
“…Table 1 listed the baseline characteristics of patients and studies. The quality of each included study was roughly assessed according to Jadad scale, four trials [16,21,34,37] were doubleblind, placebo-controlled trials, thus had a Jadad score of 5, and the remaining eleven trials were open-label controlled trials, thus had a Jadad score of 3.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 listed the baseline characteristics of patients and studies. The quality of each included study was roughly assessed according to Jadad scale, four trials [16,21,34,37] were doubleblind, placebo-controlled trials, thus had a Jadad score of 5, and the remaining eleven trials were open-label controlled trials, thus had a Jadad score of 3.…”
Section: Search Resultsmentioning
confidence: 99%
“…There were 302 LVEF decline events among these patients. The highest incidence (8.7%; 95% CI 5.3% to 13.9%) was observed in a phase III breast cancer neoadjuvant trial of trastuzumab plus lapatinib when concomitant with paclitaxel [22], while the lowest incidence was observed in four trials in which no events of LVEF decline occurred [16,27,31,37]. Using a random-effects model (χ2-based Q statistic test: Q= 31.75; p =0.004;I 2 = 55%), the summary incidence of LVEF decline in cancer patients treated with dual HER2 blockade was 4.6% (95% CI, 3.7% to 5.7%, figure 2A).…”
Section: Incidence Of Lvef Declinementioning
confidence: 93%
See 1 more Smart Citation
“…10 In HER2+ breast cancer, the addition of T to standard neoadjuvant chemotherapy significantly improved both, pathological complete response rates and event-free survival. 11 However, the question over whether the T in perioperative chemotherapy may further improve treatment outcomes in patients with localized or locally advanced resectable GC remains one of the major open questions in the current management of GC patients. Although a number of ongoing clinical studies have attempted to answer this question, the final results have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…5 A stage III ToGA clinical study showed that the efficacy of trastuzumab combined with an XP/FP regimen in patients with HER-2-positive advanced esophagogastric junction or gastric cancer was significantly better than that of patients receiving only chemotherapy. Median OS was 13.8 months (95% confidence interval [CI] [12][13][14][15][16] for patients assigned to the trastuzumab plus chemotherapy arm compared with 11.1 months (95% CI [10][11][12][13] in the chemotherapy group (hazard ratio [HR] 0.74; 95% CI 0.60--0.91; p = 0.0046). Especially in the patients with HER-2 immunohistochemistry 2 + and FISH positive or the patients with HER-2 immunohistochemistry 3 +, the survival improvement was more obvious, with the median OS better in the experimental arm (16.8 vs 11.8 months, HR: 0.65).…”
Section: Introductionmentioning
confidence: 99%